Improved Utilization of Nitrate Nitrogen Through Within-Leaf Nitrogen Allocation Trade-Offs in Leymus chinensis - Wei, Xiaowei; Yang, Yuheng; Yao, Jialiang; Han, Jiayu; Yan, Ming; Zhang, Jinwei; Shi, Yujie; Wang, Junfeng; Mu, Chunsheng (Frontiers in Plant Science, 2022)
The Sharply increasing atmospheric nitrogen (N) deposition may substantially impact the N availability and photosynthetic capacity of terrestrial plants. Determining the trade-off relationship between within-leaf N sources and allocation is therefore critical for understanding the photosynthetic response to nitrogen deposition in grassland ecosystems. We conducted field experiments to examine the effects of inorganic nitrogen addition (sole NH4+, sole NO3– and mixed NH4+/NO3–: 50%/50%) on N assimilation and allocation by Leymus chinensis. The leaf N allocated to the photosynthetic apparatus (NPSN) and chlorophyll content per unit area (Chlarea) were significantly positively correlated with the photosynthetic N-use efficiency (PNUE). The sole NO3– treatment significantly increased the plant leaf PNUE and biomass by increasing the photosynthetic N allocation and Chlarea. Under the NO3 treatment, L. chinensis plants devoted more N to their bioenergetics and light-harvesting systems to increase electron transfer. Plants reduced the cell wall N allocation or increased their soluble protein concentrations to balance growth and defense under the NO3 treatment. In the sole NH4+ treatment, however, plants decreased their N allocation to photosynthetic components but increased their N allocation to the cell wall and elsewhere. Our findings demonstrated that within-leaf N allocation optimization is a key adaptive mechanism by which plants maximize their PNUE and biomass under predicted future global changes.